A new diamond machining approach for extendable fabrication of micro-freeform lens array. (January 2018) - Zhu, Wu-Le; Duan, Fang; Zhang, Xiaodong; Zhu, Zhiwei; Ju, Bing-Feng
Abstract: Fast tool servo diamond turning is conventionally a spiral path-based process widely used to efficiently fabricate non-rotationally symmetric surfaces with ultra-fine accuracy. However, the technique is naturally restricted by the demanding bandwidth and resolution requirements, which are directly related to the complexity and size of the machining surface. Moreover, non-smooth trajectories required for machining complex lens array with discontinuities, due to overlapping sharp edges, induce vibrations causing the surface quality to deteriorate, and adding additional barriers to using this conventional technique in broader applications. In this paper, a new diamond machining approach is proposed to address its inherent drawbacks. Using the new method, complex lens array consisting of arbitrary lenslet shapes could be fabricated in an extendable way without the typical limitations. Theoretical investigations of the unique cutting kinematics, motion determination, servo synchronization and compensation will be carried out. To predict the machined surface topography, the surface generation mechanism with consideration of both the kinematic tool/workpiece interaction and elastic recovery of materials is presented. The experimental fabrication of hexagonal micro-sphere lens array, micro-freeform lens array, as well as seamlessly stitched sinusoidal surface with quadrupled areas was highly consistent and aligned with the theoretical predictions, thus demonstrating the effectiveness of the new approach and its potential for broader applications. Highlights: An innovative diamond machining approach is proposed to enable the extendable fabrication of complex lens array. Theoretical investigations of the unique cutting kinematics and surface generation mechanism are conducted. Servo synchronization and compensation method are proposed and validated. The presented approach is verified by fabrication of micro-freeform lens array and stitching machining of sinusoidal surface.